ANALISIS TINGKAT PENGETAHUAN DAN KEPATUHAN PEMILIK RESTORAN TENTANG PAJAK RESTORAN DI KECAMATAN TAMPAN - Indry Juliani; Gusnardi Gusnardi; RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the level of knowledge and compliance of restaurant owners about restaurant taxes in the Tampan district. The population in this study are all restaurants in the handsome sub-district registered at Pekanbaru BAPENDA in 2018 who have requirements such as having a menu, service quality, and employee appearance that is Employees wearing clean and polite uniforms by including company identity or logo. 38 populations were obtained and all of them were used as experiments. Data collection techniques were used observation, questionnaires and tests on restaurant owner's knowledge and compliance regarding restaurant taxes distributed to respondents. Data analysis used descriptive analysis. To test the taxpayer’s knowladge and complimance, the anlysis is used based on the average (meean) per indicator.Key Words: Knowledge of Restaurant Tax and Restaurant Tax